Profiling Distinctive Inflammatory and Redox Responses to Hydrogen Sulfide in Stretched and Stimulated Lung Cells - Sashko G. Spassov; Simone Faller; Andreas Goeft; Marc-Nicolas A. Von Itter; Andreas Birkigt; Peter Meyerhoefer; Andreas Ihle; Raphael Seiler; Stefan Schumann; Alexander Hoetzel (MDPI AG, 2022)
Hydrogen sulfide (H2S) protects against stretch-induced lung injury. However, the impact of H2S on individual cells or their crosstalk upon stretch remains unclear. Therefore, we addressed this issue in vitro using relevant lung cells. We have explored (i) the anti-inflammatory properties of H2S on epithelial (A549 and BEAS-2B), macrophage (RAW264.7) and endothelial (HUVEC) cells subjected to cycling mechanical stretch; (ii) the intercellular transduction of inflammation by co-culturing epithelial cells and macrophages (A549 and RAW264.7); (iii) the effect of H2S on neutrophils (Hoxb8) in transmigration (co-culture setup with HUVECs) and chemotaxis experiments. In stretched epithelial cells (A549, BEAS-2B), the release of interleukin-8 was not prevented by H2S treatment. However, H2S reduced macrophage inflammatory protein-2 (MIP-2) release from unstretched macrophages (RAW264.7) co-cultured with stretched epithelial cells. In stretched macrophages, H2S prevented MIP-2 release by limiting nicotinamide adenine dinucleotide phosphate oxidase-derived superoxide radicals (ROS). In endothelial cells (HUVEC), H2S inhibited interleukin-8 release and preserved endothelial integrity. In neutrophils (Hoxb8), H2S limited MIP-2-induced transmigration through endothelial monolayers, ROS formation and their chemotactic movement. H2S induces anti-inflammatory effects in a cell-type specific manner. H2S limits stretch- and/or paracrine-induced inflammatory response in endothelial, macrophage, and neutrophil cells by maintaining redox homeostasis as underlying mechanism.